Genetic difference in HLA-DR phenotypes between coeliac disease and transitory gluten intolerance. Issue 1 (January 1995) - Meuli, R; Pichler, W J; Gaze, H; Lentze, M J
Abstract : Genetic differences in HLA phenotypes were studied in coeliac disease to investigate why some patients do not react with mucosal damage after gluten challenge. Forty five children with coeliac disease and 16 with transitory gluten intolerance were typed; 76 subjects served as controls. HLA phenotypes in children with coeliac disease had significantly higher proportions of DR3/X and DR5/7 than controls (48.8% v 11.8% and 26.7% v 5.3%). Children with transitory gluten intolerance had lower DR3/X (43.8%) than children with coeliac disease and there were no DR5/7 phenotypes. Further analysis of similarly well defined cases might show whether genetic differences in the DR3/X and DR5/7 phenotypes can serve as a marker for the permanence of gluten intolerance.